2001
DOI: 10.1080/016128401750434473
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Aberrant Medical Humor by Psychiatric Unit Staff

Abstract: The purpose of this study was to develop a grounded theory about the joking behaviors of psychiatric unit staff. Fifty nine staff members (Male D 23, Female D 36), ages 28 -62, who worked in an urban, public facility were observed in unit meetings over a two year period. Data were analyzed using the constant comparative method. Participants used aberrant humor to deal with the basic social process of facing a series of ultimately unresolvable problems. The factors involved included the organizational context o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 10 publications
3
14
0
1
Order By: Relevance
“…Assumptions about what constitutes professionalism sometimes suggest that humour is not consistent with professional conduct (Sayre 2001, Sobel 2006. Our research refutes this assumption.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Assumptions about what constitutes professionalism sometimes suggest that humour is not consistent with professional conduct (Sayre 2001, Sobel 2006. Our research refutes this assumption.…”
Section: Discussionsupporting
confidence: 59%
“…Dark humour was present in both settings. Many studies of humour in health care report the prevalence of dark or gallows humour (Rosenberg 1991, Sayre 2001 which pokes fun at death or serious situations. Some (Thornton & White 1999) suggest that the more serious the situation, the greater likelihood that dark humour would appear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…68,69 Exploring these questions might improve our understanding of the sophisticated functions of humour in medical education situations, particularly if we build on existing humour research. This scholarship has established a range of functions of humour and laughter in social interactions, including as emotion management tools, 70 as a means of increasing intimacy through conversational play, 71 as a strategy for reducing stress, 72,73 as a way of modulating strong disagreements in cross-cultural settings, 74 and as a means of group demarcation. 75 As such functions suggest, power is a central feature in episodes of humour and laughter, just as it is in episodes of silence.…”
Section: Language Mattersmentioning
confidence: 99%
“…Or is it the case that certain types of humour may be less adaptive than others? Sayre (2001) studied the disparaging humour use of psychiatric nurses in relation to patients and concluded that it may have a negative impact on the therapeutic process.…”
Section: Nurses Burnout and Copingmentioning
confidence: 99%